Just-in-Time Systems - Rios, Roger; Ríos-Solís, Yasmín A. (Springer Optimization and Its Applications, 2012)
Whether different types of costs are to be reduced, benefits to be maximized or scarce resources to be managed, scheduling theory provides intelligent methods for practitioners and scientists. The just-in-time (JIT) production philosophy has enriched the classical scheduling theory with models that consider characteristics such as inventory costs, set-up times, lot sizing, or maintenance. This edited volume considers the specifics of just-in-time systems. It provides knowledge and insights on recent advances in scheduling theory where just-in-time aspects are considered. Contributions on models, theory, algorithms, and applications, that bring the theory up-to-date on the state-of-the-art of JIT systems are presented. Professionals, researchers and graduate students will find this book useful.